Maggot-Based Circular Agriculture for Economic Strengthening and Sustainable Waste Management in Kertawangi Tourism Village, West Bandung Regency - M. Rizki Fauzy; Minati Putri Larasati; Rian Andani; Dede Rusnadi; Sukmadi; Wawan Gunawan (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Absract The growing volume of organic waste in tourism villages poses a significant challenge to sustainable tourism development. Kertawangi Tourism Village in West Bandung Regency, as a community-based tourism destination, faces the problem of unmanaged household organic waste accumulation. This study aims to analyze the implementation of a circular agriculture dissemination and training program based on Black Soldier Fly (BSF) maggot cultivation, aimed at strengthening the local economy and promoting sustainable organic waste management. The study employed a descriptive qualitative approach using participatory observation, in-depth interviews, activity documentation, and direct involvement in program implementation. Findings indicate that practice-based training effectively enhanced community understanding of circular economy principles, BSF cultivation techniques, and value-added organic waste management. The program also promoted environmental awareness, created green entrepreneurship opportunities, and demonstrated potential for developing Kertawangi Tourism Village into an environmental education tourism destination within the community-based tourism framework. The study concludes that BSF maggot cultivation can serve as a replicable community-based organic waste management model, contributing to circular economy development and sustainable tourism at the village level. Keywords: Black Soldier Fly, Circular Economy, Community Empowerment, Organic Waste Management, Sustainable Tourism, Tourism Village